Divergence in Eco-Physiological Responses to Drought Mirrors the Distinct Distribution of Chamerion angustifolium Cytotypes in the Himalaya–Hengduan Mountains Region - Guo, Wen; Yang, Jie; Sun, Xu-Dong; Chen, Guang-Jie; Yang, Yong-Ping; Duan, Yuan-Wen (Frontiers in Plant Science, 2016)
Polyploid species generally occupy harsher habitats (characterized by cold, drought and/or high altitude) than diploids, but the converse was observed for Chamerion angustifolium, in which diploid plants generally inhabit higher altitudes than their polyploid derivatives. Plants at high altitudes may experience cold-induced water stress, and we therefore examined the physiological responses of diploid and hexaploid C. angustifolium to water stress to better understand the ecological differentiation of plants with different ploidy levels. We conducted a common garden experiment by subjecting seedlings of different ploidy levels to low, moderate and severe water stress. Fourteen indicators of physiological fitness were measured, and the anatomical characteristics of the leaves of each cytotype were determined. Both cytotypes were influenced by drought, and diploids exhibited higher fitness in terms of constant root:shoot ratio (R:S ratio) and maximum quantum yield of PSⅡ (Fv/Fm), less reduced maximal photosynthetic rate (Amax), transpiration rate (E), intercellular CO2 concentration (Ci) and stomatal conductance (gs), and higher long-term water use efficiency (WUEL) under severe water stress than did hexaploids. Analysis of leaf anatomy revealed morphological adjustments for tolerating water deficiency in diploids, in the form of closely packed mesophyll cells and small conduits in the midvein. Our results indicate that diploid C. angustifolium is more tolerant of drought than hexaploid plants, ensuring the successful survival of the diploid at high altitudes. This eco-physiological divergence may facilitate the species with different cytotypes to colonize new and large geographic ranges with heterogeneous environmental conditions.